Suramin attenuates dystrophin‐deficient cardiomyopathy in the mdx mouse model of duchenne muscular dystrophy. Issue 6 (11th September 2013) - De Oliveira Moreira, Drielen; Pereira, Juliano Alves; Taniguti, Ana Paula Tiemi; Matsumura, Cíntia Yuri; Ramos, Luis Alberto Ferreira; Areas, Miguel Arcanjo; Neto, Humberto Santo; Marques, Maria Julia
ABSTRACT Introduction: The purpose of this study was to determine the effects of suramin, an antifibrotic agent, on cardiac function and remodeling in mdx mice. Methods: mdx mice (8 months old) received intraperitoneal injections of suramin twice a week for 3 months. Control mdx mice (8 months old) were injected with saline. Results: Suramin improved the electrocardiography profile with the main corrections seen in S‐ to R‐wave ratio, PR interval, and Q amplitude, and a significant decrease in the cardiomyopathy index. Suramin decreased myocardial fibrosis, inflammation, and myonecrosis. Conclusions: These findings suggest that suramin may be a new adjunctive therapy to help improve cardiomyopathy in DMD. Muscle Nerve48: 911–919, 2013